Axonopsis kermanica nom. n., a new replacement name for the water mite A. iranica Pešić & Asadi, 2010 (Acari: Hydrachnidia, Aturidae) - Pešić, Vladimir; Asadi, Mahdieh (Zootaxa, 2010)
Recently, we published the name Axonopsis (Hexaxonopsis) iranica Pešić & Asadi, 2010, for a new species of water mites of the family Aturidae from Kerman Province, Iran (Asadi et al. 2010). Unfortunately, this name was already preoccupied by Pešić et al. (2009) for Axonopsis (Vicinaxonopsis) iranica Pesic, Jabaleh & Saboori, 2009, thus, the specific name A. iranica Pešić & Asadi, 2010 is a junior homonym that should be replaced by a new name (ICZN 1999). We propose a new name, Axonopsis kermanica nom. n., for the binomen Axonopsis iranica Pešić & Asadi, 2010.